An Artificial Light‐Harvesting System with Tunable Fluorescence Color in Aqueous Sodium Dodecyl Sulfonate Micellar Systems for Photochemical Catalysis. Issue 10 (28th July 2021) - Li, Xinglong; Wang, Ying; Song, Ao; Zhang, Minghui; Chen, Mengning; Jiang, Man; Yu, Shengsheng; Wang, Rongzhou; Xing, Lingbao
Main observation and conclusion: In the present work, an artificial light‐harvesting system with fluorescence resonance energy transfer (FRET) is successfully fabricated in aqueous sodium dodecyl sulfonate (SDS) micellar systems. Since the tight and orderly arrangement of dodecyl in the SDS micelles is hydrophobic, tetra ‐(4‐pyridylphenyl)ethylene (4PyTPE) can be easily encapsulated into the hydrophobic layer of SDS micelles through noncovalent interaction, which exhibits aggregation‐induced emission (AIE) phenomenon and can be used as energy donor. By using amphoteric sulforhodamine 101 (SR101) fluorescent dye attached to the negatively charged surface of SDS micelles through electrostatic interaction as energy acceptor, the light‐harvesting FRET process can be efficiently simulated. Through the steady‐state emission spectra analysis in the micelle‐mediated energy transfer from 4PyTPE to SR101, the fluorescence emission can be tuned and white light emission with CIE coordinates of (0.31, 0.29) can be successfully achieved by tuning the donor/acceptor ratio. More importantly, to better mimic natural photosynthesis, the SDS micelles with 4PyTPE and SR101 FRET system showed enhanced catalytic activity in photochemical catalysis for dehalogenation of α‐bromoacetophenone in aqueous solution and the photocatalytic reaction could be extended to gram levels. Abstract :